Peningkatkan Hasil Belajar Matematika Pada Materi Aritmatika Sosial melaui Metode Pembelajaran Bermain Peran (Role Playing) Kelas 7.9 SMPN 3 Parungpanjang - Bogor - Mursiyahtun Yulianingsih (Neolectura, 2022)
Improving Mathematics Learning Outcomes in Social Arithmetic Material Through Role Playing Learning Methods (Role Playing) Class 7.9 SMPN 3 Parungpanjang – Bogor. Bogor District Government Education Office, 2020. The background for choosing this title was due to students' difficulties in solving social arithmetic. Most of the students often have difficulty finding word problems that use the percentage principle. This resulted in low student learning outcomes. The low student achievement is the responsibility of the education apparatus, especially teachers. Therefore, it is necessary to improve various aspects in order to improve quality, especially in the field of study of mathematics. Research on improving learning outcomes really needs to be done. In its implementation, appropriate strategies and methods are needed to achieve the expected results. One way to improve student learning outcomes by using the role playing method (role playing). This study aims to improve student learning outcomes by using the role playing method, which was carried out on January 13 - February 25 2020 in class 7.9 SMPN 3 Parungpanjang - Bogor. In carrying out the research, Mrs. Tatik Irmawati, S.Kom acted as a collaborator. This study used the Action Research method which was carried out in 2 cycles, each cycle consisting of 1) Planning, 2) Implementation, 3) Observation, 4) Reflection. Quantitative data obtained from qualitative results from questionnaires, interviews, observation and documentation. The conclusion obtained from this study is that there is an increase in learning outcomes of mathematics on the subject of social arithmetic with the role playing method, namely in cycle I the average post test result is 62.94, which is 37.15% complete. and in cycle II the average post test result was 75.81, of which 62.16% was completed. From cycle I to cycle II, student learning outcomes increased by 25.01%.